Time Frame Adaptive Arbitrage: Optimizing Pairs Trading Performance with Dynamic Signal Delays - Kanber, Mustafa; Santur, Yunus (Fırat University, 2026)
This study enhances the classical z-score-based pairs trading strategy by introducing dynamic signal delay mechanisms to develop a time-adaptive approach to statistical arbitrage. Using Apple Inc. (AAPL) as a benchmark, 29 stock pairs from the Dow Jones Industrial Average (DJIA) index were analyzed to assess the impact of execution delays ranging from t+1 to t+5 on trading performance. Positions were opened and closed based on z-score signals derived from daily closing prices, where delayed execution aimed to reduce short-term market noise and optimize trade timing. Empirical results demonstrate that the proposed strategy achieved favorable performance, with 93.8% of the pairs generating positive returns and 89.7% attaining a Sharpe Ratio greater than 1.0. On average, the t+3 delay window yielded the most effective balance between risk and return, achieving a Sharpe Ratio of 2.371 and a cumulative return of 192.98%. Only 24.1% of the pairs performed best under immediate execution (t+0), highlighting the advantages of adaptive timing in arbitrage. Overall, the findings confirm that optimizing trade timing significantly enhances the profitability and stability of arbitrage models. The results provide empirical evidence supporting the potential of time-adaptive execution as a valuable improvement to traditional pairs trading frameworks.

Bu çalışma, klasik z-score tabanlı çiftli işlem (pairs trading) stratejisini dinamik sinyal gecikme mekanizmalarıyla geliştirerek istatistiksel arbitraja zaman uyarlamalı bir yaklaşım sunmaktadır. Apple Inc. (AAPL) referans alınarak, Dow Jones Industrial Average (DJIA) endeksindeki 29 hisse çifti üzerinde t+1’den t+5’e kadar farklı işlem gecikmelerinin performansa etkisi analiz edilmiştir. İşlemler, günlük kapanış fiyatlarından türetilen z-score sinyallerine göre açılıp kapatılmış; gecikmeli yürütme yaklaşımı kısa vadeli piyasa gürültüsünü azaltarak işlem zamanlamasını optimize etmeyi hedeflemiştir. Ampirik bulgular, önerilen stratejinin yüksek performans sergilediğini göstermektedir. Çiftlerin %93.8’i pozitif getiri, %89.7’si ise 1.0’ın üzerinde Sharpe Oranı elde etmiştir. Ortalama olarak t+3 gecikme penceresi en etkili risk-getiri dengesini sağlamış; 2.371 Sharpe Oranı ve %192.98 toplam getiri ile en iyi performansı göstermiştir. Yalnızca %24.1 oranındaki çiftlerde anlık (t+0) işlemler en iyi sonucu vermiştir; bu da arbitrajda uyarlanabilir zamanlamanın avantajını ortaya koymaktadır. Sonuçlar, işlem zamanlamasının optimizasyonunun arbitraj modellerinin kârlılık ve istikrarını önemli ölçüde artırdığını doğrulamaktadır. Bulgular, zaman uyarlamalı yürütme yaklaşımının geleneksel çiftli işlem çerçevelerine değerli bir katkı sunduğunu güçlü biçimde ortaya koymaktadır.
Zaman Çerçevesine Uyarlanabilir Arbitraj: Dinamik Sinyal Gecikmeleri ile İkili İşlem Performansının Optimizasyonu
Keywords: Computer Software; Bilgisayar Yazılımı